IDENTITY OF PLACE, PLACES OF IDENTITIES, CHANGE OF PLACE NAMES IN POST-APARTHEID SOUTH AFRICA - (:unkn) unknown (My University, 2007)
Various types of transformations of toponyms coexist today in South Africa at every scale: street, suburb, village, town, city, municipality, district, province and country. Place names contribute to forge the identity of particular places, at different scales. The combination between place and scale creates various sets of identities. The change of place names is a pertinent tool to analyse territorial restructuring in post-apartheid South Africa. It raises the question of multiculturalism in a ‘multilingual coexistence context'. Thus, it emphasises the question of memory of a past that new names want to rectify or to clear. Change of place names is at the intersection of spatial strategies and representations of all individuals. It is an entry point to study the evolution of today's identities in South Africa. If toponyms reflect the identity of a place, their changes are indicative of the multiple identities contained in one place or territory.
Keywords: African Research